El arbitraje : la intervención de terceros y el dictamen obligatorio (Castilla, siglos XIV y XV) (Estudios de Historia de España, 2016)
Castilian monarchy offered the arbitrage as an alternative approach for those willing to settle their disputes and therefore, it revalued the parties’ autonomy in search of an agreement. The purpose of this work is to unveil medieval arbitrage as a voluntary procedure to which all parties subject themselves in search of accepted resolutions that would surmount differences and transcend their time and characters with the rigueur of a judicial sentence. Description of the process in relation with current legislation will be sought through case study and examples of this option, open to nobility in times of controversy through neutral third parties, will be presented.
Keywords: XIVth and XVth centuries; Monarchy; Nobility; Arbitrage; Obligatory decision